2000
DOI: 10.3758/bf03198421
|View full text |Cite
|
Sign up to set email alerts
|

Divided attention, aging, and priming in exemplar generation and category verification

Abstract: Transfer-appropriate processing theories differentiate between conceptual-and perceptual-priming tasks. The former are said to be influenced by the nature of processing engaged in at study, but not by changes in modality between study and test; the latter are sensitive to changes in format between study and test, but not to variations in the extent ofsemantic processing at study. In the present experiments, we examined the effects of divided attention and aging on priming in exemplar generation and category ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
82
3
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(97 citation statements)
references
References 67 publications
8
82
3
4
Order By: Relevance
“…Other studies have indicated that divided attention reduces priming to a far lesser extent than explicit memory (e.g., Rajaram et al 2001). These relationships concern implicit memory for perceptual stimulus attributes (perceptual priming), whereas conceptual priming is reduced by divided attention to a similar extent as explicit memory (Mulligan 1998;Light et al 2000). Moreover, behavioral estimates of explicit familiarity are reduced by divided attention, but to a lesser extent than estimates of explicit recollection (Yonelinas 2001).…”
Section: Discussionmentioning
confidence: 87%
“…Other studies have indicated that divided attention reduces priming to a far lesser extent than explicit memory (e.g., Rajaram et al 2001). These relationships concern implicit memory for perceptual stimulus attributes (perceptual priming), whereas conceptual priming is reduced by divided attention to a similar extent as explicit memory (Mulligan 1998;Light et al 2000). Moreover, behavioral estimates of explicit familiarity are reduced by divided attention, but to a lesser extent than estimates of explicit recollection (Yonelinas 2001).…”
Section: Discussionmentioning
confidence: 87%
“…This result indicates that conceptual implicit memory may have more in common with conceptual explicit memory than with perceptual implicit memory. Similar effects of divided attention at encoding on category exemplar generation have been found by other researchers as well (e.g., Light, Prull, & Kennison, 2000). Thus, conceptual implicit memory appears to be measurable in normal participants, but it is difficult to isolate from the influences of explicit retrieval (whether intentional or unintentional), and it is difficult to test without participants' awareness.…”
mentioning
confidence: 79%
“…Horton and colleagues (Horton, Wilson, & Evans, 2001;Horton, Wilson, Vonk, Kirby, & Nielsen, 2005) have recently used RT data to demonstrate that explicit retrieval was not used in their tests of conceptual implicit memory. Other researchers (e.g., Light et al, 2000;Zeelenberg, 2005) have also demonstrated that RT is a valuable measure of conceptual implicit memory.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies (Light, Prull, & Kennison, 2000;Vaidya et al, 1997) have reported that category verification, a task similar to semantic classification, does not respond to levelsof-processing manipulation. In their experiments, a conceptual task different from the category verification was used task during study.…”
Section: Discussionmentioning
confidence: 99%